Meningkatkan Konsentrasi Anak Melalui Metode Eksperimen Mencampur Warna Pada Anak Usia 5-6 Tahun - Sukma Wijayanti, Deri; Kusuma Dewi, Berliana; Yunsa Nurhasanah, Alwin (UIN Fatmawati Sukarno Bengkulu, 2025)
The type of research used is Classroom Action Research (PTK) which is an approach to improving learning practices in the classroom. The stages of the PTK cycle include problem identification, planning action, implementation, observation, evaluation, reflection, and adjustments for the next cycle. The main tool used is an observation form, which collects data during the learning process with a checklist as a guide. PTK data analysis includes descriptive analysis, quantitative and qualitative analysis, as well as data triangulation to support learning improvement. With this approach, PTK provides important insights to improve classroom learning. The results of the research show that through the experimental method of mixing colors, it has been proven to increase the concentration of children aged 5-6 years. Significant increases were seen in each concentration indicator from cycle to cycle. Starting from a concentration level that reached 35.75% in the pre-cycle, it rose to 55.75% in the first cycle of the second meeting, and increased again to 64.25% in the first cycle of the second meeting. In cycle II, there was a greater increase, with the concentration level reaching 83.75% at meeting I and 86.75% at meeting II. In addition, there was a significant increase in the creativity indicator, increasing to 83.3%, indicating an increase in children's creativity. This change was caused by the direct approach in the second cycle which gained more children's interest in the games being played, compared to the first cycle.